Effect of Ultrasound on Parthenogenic Activation of Mouse Oocyte - Hamid Gurabi; Ahmad Vosough Taqi Dizaj; Nahid Nasiri; Darush Hamrahi; Firoozeh Ahmadi; Poopak Eftekhari-Yazdi (Cell Journal, 2010)
Objective: Artificial stimulation of mouse oocyte, in the absence of sperm contribution,can induce its parthenogenic activation of oocyte. Ultrasound is one of the newest methodsfor artificial activation of mammal oocytes, and its successful utilization in pig oocyteactivation has been recently reported. Our objective was to assess the effect of ultrasoundon mouse oocyte activation.Materials and Methods: Our groups included1 control group, 3 experimental groups consistingof 1, 2 and 3 repetitions of ultrasound exposure, and 3 sham groups handled similarto experimental groups but ultrasound system was off during treatments.In experimental groups, adult female NMRI mice at the interval between pregnant mareserum gonadotropin (PMSG) and human corionic gonadotropin (hCG) injections, wereexposed to continuous ultrasound with 3.28 MHz frequency and peak intensity (Ipk) = 355mW/cm2.Sixteen hours after injection of hCG, the mice were euthanized and their oocytes werecollected; thereafter, parthenogenic oocytes were counted.Results: Data analysis using the ANOVA test shows a significant increase in the number ofparthenogenic oocytes in mice with 3 overall exposures to ovarian ultrasound (p<0.05).A significant decrease in the number of metaphase II (MII) oocytes numbers was alsoseen in mice treated with ultrasound (p<0.05).Conclusion: Ultrasound is thought to induce pores generation in oocyte membranes andprovides an easier inward transport of Ca++ into oocytes. This phenomenon can inducemeiosis resumption in immature oocytes. With increased exposure repetitions from 1 to 3times and greater Ca++ arrival, oocytes can be parthenogenetically activated.